Hubungan Tingkat Pengetahuan dengan Perilaku Cuci Tangan Menggunakan Handrub pada Keluarga Pasien di Ruang Bedah RSUD dr. H. Moh. Anwar Sumenep - Elyk Dwi Mumpuningtias; Sugesti Aliftitah; Illiyini Illiyini (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Hand hygiene is a core element for protecting patients against nosocomial infection. Hand hygiene by alcohol-based hand rub is a simple and quick procedure that takes only a few seconds. The problem in this research is there were so many patient’s families who had not been using handrub liquid although the hospital already provide it, especially in Bedah Room RSUD dr. H. Moh. Anwar Sumenep. The aim of this research is to analyze the correlation between knowledge level with hand hygiene behavior using handrub on patient’s family in Bedah Room RSUD dr. H. Moh. Anwar Sumenep. The design of this study was analytic with cross sectional design. The population in this research was the entire patient’s family in Bedah Room RSUD dr. H. Moh. Anwar Sumenep. The number of samples was 60 people of patient’s family and sample was selected by Purposive Sampling technique. The independent variable is knowledge level and the dependent variable is hand hygiene behavior using handrub on patient’s family. The data collected by using questionnaires and observation sheets. The research result shows that mostly of patient’s family has deficient knowledge level, that was 44 people (73,3%) and almost all of respondents did not do hand hygiene using handrub, that was 49 people (81,7%). The result of statistic test by Fisher’s Exact test is obtained P value <α (0.000 < 0.05). So, there is a correlation between knowledge level with hand hygiene behavior using handrub on patient’s family in Surgery Room RSUD dr. H. Moh. Anwar Sumenep. Therefore, the level of knowledge can affect hand hygiene behavior using handrub to avoid disease threat and nosocomial infection, good knowledge level is needed. Keywords: Knowledge, Hand Hygiene Behavior, Handrub